Recent Advances in Helicobacter pylori Infection in Children: From the Petri Dish to the Playgound - Peng-Yuan Zheng; Nicola L Jones (Canadian Journal of Gastroenterology)
Helicobacter pylori infection is acquired in childhood, plays a causative role in chronic gastritis and peptic ulcer disease, and is associated with the development of gastric cancer. The present review focuses on recent advances in the scientific knowledge of H pylori infection in children, including clinical sequelae, diagnosis and treatment. In addition, recent insights regarding both bacterial and host factors that mediate human diseases associated with H pylori infection are discussed.